The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5539/elt.v10n12p134
|View full text |Cite
|
Sign up to set email alerts
|

Using Online Computer Games in the ELT Classroom: A Case Study

Abstract: The purpose of this research was to investigate the effectiveness of computer games in learning English as a foreign language and the extent to which they increase motivation in young students. More particularly, this research investigated the validity of the hypothesis that computer games are a particularly motivating means for young students to learn English vocabulary effectively in comparison to other approaches suggested by the Greek National Curriculum. The grade, in which this research was conducted, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…A number of authors have researched the effect of MGBLLAs on EFL teaching and learning from the perspective of learners' motivation (Alamer, 2016;Avila, 2015;Beserra et al, 2017;Cam & Tran, 2017;De Freitas, 2006;Ebrahimzadeh & Alavi, 2016;Gozcu & Caganaga, 2016;Vasileiadou & Makrina, 2017;Saha & Singh, 2016). In their study of the (SoLoMo) game-based application, Lin et al's (2018) experimental group, which used the gaming application recorded better learning outcomes and increased motivation.…”
Section: Utilizing Mgbllas To Enhance Efl Learning Motivationmentioning
confidence: 99%
“…A number of authors have researched the effect of MGBLLAs on EFL teaching and learning from the perspective of learners' motivation (Alamer, 2016;Avila, 2015;Beserra et al, 2017;Cam & Tran, 2017;De Freitas, 2006;Ebrahimzadeh & Alavi, 2016;Gozcu & Caganaga, 2016;Vasileiadou & Makrina, 2017;Saha & Singh, 2016). In their study of the (SoLoMo) game-based application, Lin et al's (2018) experimental group, which used the gaming application recorded better learning outcomes and increased motivation.…”
Section: Utilizing Mgbllas To Enhance Efl Learning Motivationmentioning
confidence: 99%
“…Pupils are always eager to play games while learning when they successfully operating the games. Vasileiadou and Makrina (2017) confirmed that games are motivating and it is an effective resource. The resource will assist the pupils in improving ESL vocabulary and keep them interested with full of excitement (Vasileiadou & Makrina, 2017).…”
Section: Discussionmentioning
confidence: 78%
“…Scientific textbooks have been written on using games on learning target language vocabulary (Vasileiadou & Makrina, 2017). Likewise, Ashraf et al (2014) deal with games' effect on children's vocabulary learning.…”
Section: Literature Reviewmentioning
confidence: 99%